A TGFβ-Smad4-Fgf6 signaling cascade controls myogenic differentiation and myoblast fusion during tongue development - Han, Dong (Company of Biologists, 2012)
The tongue is a muscular organ and plays a crucial role in speech, deglutition and taste. Despite the important physiological functions of the tongue, little is known about the regulatory mechanisms of tongue muscle development. TGFβ family members play important roles in regulating myogenesis, but the functional significance of Smad-dependent TGFβ signaling in regulating tongue skeletal muscle development remains unclear. In this study, we have investigated Smad4-mediated TGFβ signaling in the development of occipital somite-derived myogenic progenitors during tongue morphogenesis through tissue-specific inactivation of Smad4 (using Myf5-Cre;Smad4(flox/flox) mice). During the initiation of tongue development, cranial neural crest (CNC) cells occupy the tongue buds before myogenic progenitors migrate into the tongue primordium, suggesting that CNC cells play an instructive role in guiding tongue muscle development. Moreover, ablation of Smad4 results in defects in myogenic terminal differentiation and myoblast fusion. Despite compromised muscle differentiation, tendon formation appears unaffected in the tongue of Myf5-Cre;Smad4(flox/flox) mice, suggesting that the differentiation and maintenance of CNC-derived tendon cells are independent of Smad4-mediated signaling in myogenic cells in the tongue. Furthermore, loss of Smad4 results in a significant reduction in expression of several members of the FGF family, including Fgf6 and Fgfr4. Exogenous Fgf6 partially rescues the tongue myoblast fusion defect of Myf5-Cre;Smad4(flox/flox) mice. Taken together, our study demonstrates that a TGFβ-Smad4-Fgf6 signaling cascade plays a crucial role in myogenic cell fate determination and lineage progression during tongue myogenesis.